Brachytherapy in organ-preserving treatment of choroidal melanoma: complications and the possibility of their prediction - A. A. Bykhovsky; I. E. Panova; E. V. Samkovich (Acta Biomedica Scientifica)
This review analyzed the domestic and foreign literature on brachytherapy of choroidal melanoma using ruthenium ophthalmic applicators. The review highlights the historical aspects of radiation treatment, from the first experience of using ionizing radiation in the treatment of malignant neoplasms to modern methods of brachytherapy; presents the radiobiological foundations of radiation therapy; considers the issues of radiation pathomorphosis, reflecting the nature of pathological changes in the choroidal melanoma tissue during brachytherapy; shows the dependence of the effect of exposure ionizing radiation from the phase of the cycle of cell division; and also describes the presence of changes characteristic of the response to ionizing radiation in unirradiated tissues. The analysis of various post-radiation complications, both early and late, was carried out in some detail, with emphasis on the possibility of predicting and preventing them in real clinical practice. A comparison is made in terms of the frequency of development of various post-radiation complications in the works of domestic and foreign authors, as well as a comparison with the effect of ionizing radiation from other radioactive isotopes. Recommendations of experts are given regarding the correct calculation of the dose to the sclera and medication support, based on many years of experience in the use of ruthenium ophthalmic applicators for brachytherapy of choroidal melanoma. The risks of developing such late complications as radiation maculopathy and radiation neuropathy have been demonstrated, especially in pre-equatorial tumor localization. The possibilities of modern methods of instrumental diagnostics for studying the processes occurring in the area of the tumor, as well as changes in the surrounding tissues, are shown, which determines the feasibility and importance of further study of this issue.